Investigation of the riddle of sulfathiazole polymorphism - Abu Bakar, Mohd Rushdi; Nagy, Zoltan K.; Rielly, Chris D.; Dann, Sandy E. (Elsevier, 2011)
Since the discovery of sulfathiazole as an antimicrobial agent in 1939, numerous works in the screening for its different polymorphic forms, which is an essential part of drug development, have been conducted and published. These works consequently result in the availability of various methods for generating a particular polymorph. By following these methods, however, one cannot be guaranteed to obtain the intended pure polymorph because most of the methods do not clearly and adequately describe the crystallization conditions, such as cooling rates and initial solute concentrations. In this paper, the available methods for generating all the known polymorphs of sulfathiazole are reviewed and selected methods for generating certain polymorphs, performed with their processes monitored using process analytical technology tools, i.e. focussed beam reflectance measurement and attenuated total reflectance ultraviolet spectroscopy, are presented. The properties of the obtained crystals, examined using various characterisation methods, are also presented and whenever possible, are compared with those of other workers.